Formation of Ti-Al-Cr-B-N Coatings by Ion-Magnetron Sputtering of Composite Targets; AIP Conference Proceedings; Vol. 1909 : Advanced Materials with Hierarchical Structure for New Technologies and Reliable Structures 2017 (AMHS’17) - Sergeev O. V. Oleg; Kalashnikov M. P. Mark Petrovich; Voronov A. V. Andrey; Sergeev V. P. Viktor Petrovich; Panin V. E. Viktor Evgenyevich (2017, 2017)
Title screen